PERBANDINGAN TINGKAT KEBUGARAN JASMANI SISWA BERDASARKAN POLA TRANSPORTASI KE SEKOLAH YANG BERBEDA (STUDI PADA KELAS VIII SMP NEGERI 3 SAMPANG) - SHOLIHIN, MOH. (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education health sports have an important role in the formation of the whole person. The implementation of physical education in schools is a form of physical fitness coaching for children and adolescents. Physical fitness needed by a child is different from that required adult. To identify and assess the person's level of physical fitness can be implemented with physical fitness test, therefore, Physical Fitness Test Indonesia (TKJI) is very important in learning physical education health sports. Physical fitness is one of the purposes of the implementation of the education. The purpose of this study was to determine: 1) differences in the level of physical fitness of students based on the pattern of transport to a different school studies in class VIII the state junior high school 3 Sampang; 2) how much difference in the level of physical fitness of students based on the pattern of transport to different schools in study class VIII the state junior high school 3 Sampang. Objectives of this study were students who bike, walk, and take public transportation on eighth grade students of the state junior high school 3 Sampang by the number of samples taken by 90 students, each student to and from school by biking, walking, and taking public transportation as many as 30. The method in this analysis using statistical methods and quantitative descriptive Anova test (One - Way ANOVA), while the data collection is done by using the Indonesian Physical Fitness Test (TKJI). The research concluded that: 1) Physical fitness of students to and from school by walking an average value of 12.70. For students with work for entire world cycling has an average of 15.77. While students with public transit has an average value of 13.30. 2) The results of the analysis one-way ANOVA test obtained: tcount (6008)> Table (1664). In other words that there is a significant difference in students' physical fitness levels based on the pattern of different transport to school studies in class VIII the state junior high school 3 Sampang. Keywords: physical fitness, transportation patterns